2021
DOI: 10.1186/s12884-020-03537-z
|View full text |Cite
|
Sign up to set email alerts
|

Reconciling relationships with physical activity: a qualitative study of women’s postnatal physical activity decision-making

Abstract: Background Challenges with engaging in postnatal physical activity can negatively affect the health of women and their families. This study investigated women’s physical activity decision-making processes and strategies to support their physical activity as part of a healthy postpartum transition. Methods Thirty healthy women with infants aged 2.5–12 months completed 3-day activity diaries and an individual interview. Using Glaser and Charmaz’s gro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…It is important to also note that over half of our mothers gave birth by caesarean section which may have a divergent recovery path compared to vaginal birth (Roy, 2014 ) and be further reflected in physical activity confidence. Liva et al ( 2021 ) found that new mothers struggled to gauge appropriate physical activity engagement which led to over or underestimating personal capacity for physical activity. In post-program interviews immediately after our intervention, participants noted an increase in confidence in engaging in physical activity with a specific improvement in capability to be active with their baby.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is important to also note that over half of our mothers gave birth by caesarean section which may have a divergent recovery path compared to vaginal birth (Roy, 2014 ) and be further reflected in physical activity confidence. Liva et al ( 2021 ) found that new mothers struggled to gauge appropriate physical activity engagement which led to over or underestimating personal capacity for physical activity. In post-program interviews immediately after our intervention, participants noted an increase in confidence in engaging in physical activity with a specific improvement in capability to be active with their baby.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that women who chose to participate in the exercise program were likely more physically active and confident than those who did not contact us to participate. New mothers who consider physical activity to be central to their well-being seek out physical activity options (Liva et al, 2021 ) and therefore create a voluntary bias. Future research therefore needs to expand recruitment to ensure that a broad population of postpartum women participate in specialized physical activity programming to determine its appropriateness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of postpartum PA include the maintenance and improvement of mental health in addition to physical recovery [ 6 , 7 ]. However, many obstacles that prevent women from engaging in PA have been reported [ 8 ]. These obstacles include the lack of time [ 9 13 ], issues with child care [ 9 ], fatigue, and poor physical condition [ 9 , 12 ], social isolation [ 11 ], being overwhelmed by motherhood responsibilities [ 11 ], lack of motivation [ 11 , 12 ], lack of appropriate exercise facilities, and lack of professional advice on exercise [ 11 ].…”
Section: Introductionmentioning
confidence: 99%